Arab nationalism in the twentieth century : from triumph to despair - Dawisha, A. I. (Princeton University Press, 2016)
Publisher's description: Like a great dynasty that falls to ruin and is eventually remembered more for its faults than its feats, Arab nationalism is remembered mostly for its humiliating rout in the 1967 Six Day War, for inter-Arab divisions, and for words and actions distinguished by their meagerness. But people tend to forget the majesty that Arab nationalism once was. In this elegantly narrated and richly documented book, Adeed Dawisha brings this majesty to life through a sweeping historical account of its dramatic rise and fall. Dawisha argues that Arab nationalism--which, he says, was inspired by nineteenth-century German Romantic nationalism--really took root after World War I and not in the nineteenth century, as many believe, and that it blossomed only in the 1950s and 1960s under the charismatic leadership of Egypt's Gamal 'Abd al-Nasir. He traces the ideology's passage from the collapse of the Ottoman Empire through its triumphant ascendancy in the late 1950s with the unity of Egypt and Syria and with the nationalist revolution of Iraq, to the mortal blow it received in the 1967 Arab defeat by Israel, and its eventual eclipse. Dawisha criticizes the common failure to distinguish between the broader, cultural phenomenon of "Arabism" and the political, secular desire for a united Arab state that defined Arab nationalism. In recent decades competitive ideologies--not least, Islamic militancy--have inexorably supplanted the latter, he contends. Dawisha, who grew up in Iraq during the heyday of Arab nationalism, infuses his work with rare personal insight and extraordinary historical breadth. In addition to Western sources, he draws on an unprecedented wealth of Arab political memoirs and studies to tell the fascinating story of one of the most colorful and significant periods of the contemporary Arab world. In doing so, he also gives us the means to more fully understand trends in the region today